Дене тәрбиясында баскетбол – спорт ойынының тәлим – тәрбиялық әҳмийети (SCIENCE and SOCIETY, 2017)
The article is devoted to the study of such kind of sport as basketball, its physiological and psychological peculiarities. The author also studies the the hygienic, educational and upbringing significance of this kind of sport. There have been analyzed the activity of Basketball Federation is Uzbeki- stan and doing basketball exercises from the theoretical point of view.